Acceleration analysis of 6-RR-RP-RR parallel manipulator with offset hinges by means of a hybrid method. (March 2022) - Zhang, Yang; Han, Hasiaoqier; Zhang, Hui; Xu, Zhenbang; Xiong, Yan; Han, Kang; Li, Yaobin
Highlights: The modeling of the 6-RR-RP -RR parallel manipulator is proposed. The displacement analysis is solved via the Denavit-Hartenberg method. Velocity and acceleration are analyzed using the differential transformation method. The derived equations can be easily translated into computer programs. The theoretical results are very consistent with the simulation results. Abstract: In this work, the kinematics of a symmetrical hexapod parallel manipulator is investigated by means of Denavit-Hartenberg method and differential transformation method. When compared with a general Gough-Stewart platform, the limbs of the parallel manipulator are connected to the mobile and fixed platforms through offset hinges, rather than traditional spherical and universal hinges. Because the offset variable of the hinge axis are introduced by the offset hinge, the kinematics of the parallel manipulator studied becomes more complicated. The forward and inverse displacement analysis are approached by means of the Denavit-Hartenberg method. Then, the velocity and acceleration are analyzed using differential transformation method. The concise expression is obtained and can be easily translated into computer program. The derivation of acceleration analysis of the 6-RR-RP -RR parallel manipulator using the hybrid approach is novel in this research field. Finally, a numerical example is given and the numerical results are verified via co-simulation.